Length of Bowel Rest Does Not Predict Gastrojejunostomy Tube-Associated Intussusception Recurrence. Issue 3 (27th December 2022) - Abebe, Abel Tsehay; Worede, Fikadu; Elsingergy, Mohamed; Cahill, Anne Marie; Acord, Michael R.
Abstract : Objectives: One potential treatment for gastrojejunostomy (GJ) tube-related intussusception is bowel rest, whereby the GJ tube is replaced with a gastrostomy tube. The aim of this study was to determine whether bowel rest length was associated with decreased risk of re-intussusception. Methods: Pediatric patients with GJ tube-related intussusceptions were identified during the study period of January 1, 2010 and August 1, 2021. Records were reviewed for demographics, symptoms, need for central access to initiate parenteral nutrition, and length of stay. Comparison was made between patients with intussusception recurrence within 30 days and those without. Those undergoing earlier replacement, defined as the first quartile of rest time, or 72 hours, were then compared to longer periods of bowel rest. Results: Forty-six intussusceptions were included, with a median age of 2.8 years (interquartile range, IQR: 1.4–4.1) and weight of 12 kg (IQR: 8.9–15.4). All patients diagnosed as outpatient (54.3%) required hospital admission and 9 of 46 (19.6%) required central access. There were 7 recurrences (15.2%). There was no difference in recurrence based on time of bowel rest (5 days in those without vs 6 days in those with, P = 0.30) nor a difference in recurrence with <72 hours of bowel rest compared to >72 hours (1/15, 6.7% vs 6/31, 19.3%). Patients undergoing earlier exchange had a shorter median length of hospital stay (3 vs 8.5 days, P = 0.003). Conclusion: Length of bowel rest was not associated with recurrent GJ tube-related intussusceptions. If bowel rest is utilized, <72 hours may be sufficient to decrease length of hospital stay.